Pelatihan Zoom Meetings dan Streaming Youtube untuk Pengembangan Komunitas Ngaji Online - Nada Arina Romli; Dini Safitri; Suci Nurpratiwi; Lukman Hakim (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This community service aims to improve skills and provide knowledge for majelis taklim members about using Zoom meeting for the virtual event and broadcasting virtual events through Youtube streaming service in Malaka Jaya District, Jakarta City. Method: This community service applied an interactive method with survey location, finding community problems with interview methods and training methods to provide knowledge and improve the majelis taklim community of Malaka Jaya District, Jakarta City. Results: Organizing online meetings with Zoom meetings can provide solutions to majelis taklim community during the Covid-19 pandemic, where the implementation of studies can still be held without face-to-face. It supports government movements to prevent the transmission of the Covid-19 virus. In addition, broadcasting a study event by streaming on a Youtube channel can have a broad impact on the general public. Conclusion: Training on Zoom meetings and Youtube streaming can develop a wider online islamic learning community.